INCREASING AWARENESS OF CHRONIC DISEASE SUFFERERS IN PARTICIPATING IN THE PROLANIS ACTIVITY PROGRAM AT THE MEUREUBO HEALTH CENTER, WEST ACEH REGENCY - Wizra Lutia (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
This survey was conducted at the Meureubo Health Center in West Aceh Regency with the aim of seeing the increase in awareness of prolanis sufferers at the Meureubo Health Center in West Aceh Regency in participating in the prolanis activity program. Awareness for people with chronic diseases is very necessary to do so as not to cause complications, by following prolanis. BPJS Kesehatan has also implemented a chronic disease management program (prolanis) for the management of hypertension and type 2 diabetes mellitus. Since 2014. In 2021 the Meureubo Health Center has 217 people with hypertension and type 2 diabetes mellitus, with 32 patients, plus in 2022 the disease hypertension to 543 patients. The purpose of this study was to determine the increase in awareness of chronic disease sufferers in participating in the Prolanis program organized by BPJS Kesehatan Meulaboh Branch and run by the Meureubo Health Center. This type of research is a case study qualitative research design (case study).